Children and childhood: unveiling the universes - Elaine de Paula (Universidade Federal de Santa Catarina, 2004)
The reflections made throughout this text is an attempt to understand the infant universe, based on the premise that children are active subjects and, therefore, critical and (co) construction of their "worlds." Although not part of the world of adults, or unrelated to the cultural artifacts displayed by the company, the children, "to their fashion," re reality to understand it better, or as Walter Benjamin would say, build a small world is in the large .